PENGARUH PENERAPAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS VIII SMP NEGERI 3 KOTA SOLOK - REFO MONIKA (Jurnal Edukasi dan Penelitian Matematika, 2020)
Mathematical communication skills of class VIII students in SMP Negeri 3 Solok City are still low. This is seen by giving problems with mathematical communication indicators. One learningnmodelnthatncannbenusedntonovercome these problems is Problem Based Learning (PBL). Thenpurposenofnthisnstudynwasntonanalyze and describe the development of mathematical communicationnskillsnofnstudentsnin class VIII of SMP Negeri 3 Solok City who learned to use the PBL model. Thisntypenofnresearchnisna quasy-experimental study withnanrandomized posttest groupnonlyndesign. Thenresultsnofnthendatananalysisnshowednthatntherenwasnanneffect ofnthe application of the PBL model to students' mathematical communication skills, sonthatnthe mathematicalvcommunicationnskillsnofnstudentsvwhonlearned with PBL models werenbetternthan thenmathematicalncommunicationnskillsnofnstudentsnwho studied with conventionalnlearningnin classnVIIInofvSMPnNegerin3 SoloknCity.Keywords — Problem Based Learning, mathematical communication skills